Case Report: Factor VII Deficiency Presented With Cephalohematoma After Birth - Lo, Yuan-Chun; Peng, Ching-Tien; Chen, Yin-Ting (Frontiers in Pediatrics, 2021)
Introduction: Factor VII deficiency is a rare inherited autosomal recessive bleeding disorder with a global prevalence of 1/500000. Most cases remain asymptomatic, whereas cases with severe clinical presentation are rarely reported. Case presentation: A newborn male with no relevant maternal antenatal history delivered via vacuum-assisted caesarean section presented with a large cephalohematoma after delivery. Poor appetite, pale appearance, and bulging fontanelle were observed 2 days later, progressing to hypovolemic shock. Further imaging examination revealed a large intracranial hemorrhage. Serial laboratory examination revealed remarkable coagulopathy with prolonged PT and factor VII deficiency (< 1%, severe type). The patient was genetically confirmed to have FVII:c 681+1 G>T homozygous mutation. Brain hemorrhage resolved with high-dose factor VII replacement therapy. However, repeated hemothorax and intracranial hemorrhage were detected despite prophylactic therapy. Therefore, the patient was under regular factor VII supplementation with a rehabilitation program for cerebral palsy. Conclusions: A case of factor VII deficiency with large cephalohematoma and intracranial hemorrhage after birth has been described, which was treated with high-dose replacement therapy. Variants of the FVII:c 681+1 G>T (IVS6+1G>T) homozygous genotype may present with a severe phenotype at the neonatal stage. We aimed to share a unique neonatal presentation with a certain genotype and treatment experience with initial replacement therapy followed by regular prophylactic dosage.